Students’ Errors in Solving Contextual Linear Programming Problems Based on Brodie’s Theory Viewed from Self-Efficacy - Aswin, Aswin; Salido, Achmad; Meiliati, Rafika; Husain, Dayana Sabila; Khairunnisa, Khairunnisa (Media Pendidikan Matematika, 2026)
This study aims to analyze students’ errors in solving contextual mathematics problems on linear programming, based on Brodie’s theory, through the lens of students’ self-efficacy. Previous studies have generally used Newman Error Analysis and focused more on the procedural stages of problem-solving, whereas studies integrating Brodie’s theory with self-efficacy in solving contextual problems remain limited. This study offers a novel approach, an error analysis that integrates cognitive and affective aspects to gain a more comprehensive understanding of student errors. The study employs a qualitative case study design. It was conducted at a high school in Bulukumba, with a student population of 36. Subjects were selected purposively: three students representing the high-, moderate-, and low-self-efficacy categories. Research instruments included contextual problem-solving tests, a self-efficacy questionnaire, interviews, observations, and documentation. Data analysis was conducted using the Miles and Huberman model, with the stages of data reduction, data presentation, and conclusion drawing, and triangulation to ensure data validity. The results of the study indicate that students with high self-efficacy made only basic errors, such as errors in examples and failure to write conclusions. Students with moderate self-efficacy made basic errors, had missing information, and made appropriate errors, while students with low self-efficacy made a wider variety of errors, namely basic errors, appropriate errors, missing information, and partial insight. These findings indicate that self-efficacy influences the types and levels of errors students make when solving contextual problems. Therefore, improving self-efficacy needs to be a focus in mathematics learning to minimize problem-solving errors.